Texts, Contexts and Intertextuality Dickens as a Reader - Lennartz, Norbert; Koch, Dieter (2014)
While Dickens used to be seen as a writer of shallow and sentimental children's literature, as the prolific caterer to the new market of mass literature, this collection of essays shows that Dickens was not only a reader of high-brow literature, but also expected his readers to understand them in the context of contemporary scientific and economic debates. Covering a wide range of writers - from Sidney, Shakespeare, Cervantes to Swift, Smollett and Bulwer-Lytton - Dickens's novels reveal a multi-layered cosmos and supply their readers with richly woven nets of intertextuality.